2007
DOI: 10.1364/ao.46.002401
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating chromatic aberration in Gauss-type lens design using a novel genetic algorithm

Abstract: Two different types of Gauss lens design, which effectively eliminate primary chromatic aberration, are presented using an efficient genetic algorithm (GA). The current GA has to deal with too many targets in optical global optimization so that the performance is not much improved. Generally speaking, achromatic aberrations have a great relationship with variable glass sets for all elements. For optics whose design is roughly convergent, glass sets for optics will play a significant role in axial and lateral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Different evolutionary optimization approaches have been used in lens design: genetic algorithms [16][17][18][19][20][21][22][23], evolution strategy [16][17][18][19][20][21][22][23][24][25], genetic programming [21,26,27], and evolutionary programming [28]. All of these studies have reported good results.…”
Section: Evolutionary Optimization Methods and Their Use In Optical Dmentioning
confidence: 99%
“…Different evolutionary optimization approaches have been used in lens design: genetic algorithms [16][17][18][19][20][21][22][23], evolution strategy [16][17][18][19][20][21][22][23][24][25], genetic programming [21,26,27], and evolutionary programming [28]. All of these studies have reported good results.…”
Section: Evolutionary Optimization Methods and Their Use In Optical Dmentioning
confidence: 99%
“…This study proposes combining a neural network (NN) algorithm [11][12][13] with a genetic algorithm (GA) [14,15] to optimize the SA, TCO, and MTF values of contact lenses; this method is called the NN-GA [16][17][18][19]. The purpose of this study was to apply optical design theory and an optimization algorithm method of optimal processing to select contact lens parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, three design goals are followed: light efficiency, uniformity and volumetric size with a weighting of 1:1:1. Optimization work by the Taguchi method, which is believed to extend optimization following the normal optimization method by damping least square (DLS) [2], significantly improves the system performance and volumetric size. The extended optimized parameter design is able to improve the luminous flux by 4.84%, the illumination uniformity 5.62% and the packing size by 12%.…”
Section: Introductionmentioning
confidence: 99%